The effect of melatonin on hearts in ischemia/reperfusion experiments without and with HTK cardioplegia - Schäfer, Michael; Gebhard, Martha-Maria; Gross, Wolfgang (Bioelectrochemistry, 2019)
Our aim was to investigate if the cardioplegic solution HTK can be improved by the addition of the ROS scavenger melatonin. 158 guinea pig hearts without (UI80) or with HTK protection (HTK80) were investigated in ischemia/reperfusion experiments. Ischemia lasted 80min at 30°C. Melatonin was given before ischemia (UI80+M1, HTK80+M1) or before and after ischemia (UI80+M2, HTK80+M2). We measured the left ventricular developed pressure (LVDP), diastolic pressure (LVPmin), cardiac rhythm (VC-RR), time of electrical cell uncoupling (t-in) and recovery (t-ret), intracellular Ca++ [Ca++], and postischemic ROS. After 45min reperfusion, LVDP in UI80 was significantly higher than in HTK80 (p<.01). Compared to UI80, the postischemic ROS burst was slightly smaller in HTK80 and significantly smaller in HTK80+M1 and HTK80+M2 (p<.05). Melatonin had no effect on LVPmin, t-in, t-ret, [Ca++], and on LVDP in groups UI80+M1 and HTK80+M1, improved slightly VC-RR (n. s.) but significantly decreased LVDP in the groups UI80+M2 and HTK80+M2 (p<.01). With melatonin we were able to attenuate the postischemic ROS burst, but the tissue damage by ROS seemed to be less important for the chosen ischemia condition because melatonin was unable to improve the functional recovery during reperfusion of HTK protected hearts.
Gesehen am 29.10.2019